2000
DOI: 10.1074/jbc.275.11.7597
|View full text |Cite
|
Sign up to set email alerts
|

Tsc3p Is an 80-Amino Acid Protein Associated with Serine Palmitoyltransferase and Required for Optimal Enzyme Activity

Abstract: Serine palmitoyltransferase catalyzes the first step of sphingolipid synthesis, condensation of serine and palmitoyl CoA to form the long chain base 3-ketosphinganine. The LCB1/TSC2 and LCB2/TSC1 genes encode homologous proteins of the ␣-oxoamine synthase family required for serine palmitoyltransferase activity. The other ␣-oxoamine synthases are soluble homodimers, but serine palmitoyltransferase is a membrane-associated enzyme composed of at least two subunits, Lcb1p and Lcb2p. Here, we report the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
196
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 179 publications
(202 citation statements)
references
References 21 publications
4
196
1
Order By: Relevance
“…It has been suggested that LCB2 acts as the enzymatically active center, and LCB1 appears to stabilize the heterodimer [14]. The lcb1 mutations caused a substantially reduced level of the LCB2 protein in both a Chinese hamster ovary cell mutant line [43] and yeast cells [44], thus leading to lethality in both cases. Similarly, the lcb1-1 mutation causes an embryolethal phenotype, indicating an essential role of FBR11 in plant growth and development [41].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that LCB2 acts as the enzymatically active center, and LCB1 appears to stabilize the heterodimer [14]. The lcb1 mutations caused a substantially reduced level of the LCB2 protein in both a Chinese hamster ovary cell mutant line [43] and yeast cells [44], thus leading to lethality in both cases. Similarly, the lcb1-1 mutation causes an embryolethal phenotype, indicating an essential role of FBR11 in plant growth and development [41].…”
Section: Discussionmentioning
confidence: 99%
“…For determination of SPT activity, a reaction containing 50 mM Hepes (pH 8.1), 50 M pyridoxyl phosphate, 2 mM NADPH, 2 mM NADH, 10 mM L-[G-3 H]serine (10 Ci/mL), 75 or 100 M acyl-CoA, and 0.2-0.4 mg of microsomal membranes was incubated at 37°C for 10 min. The reaction was stopped and the products were extracted and quantified as described (4).…”
Section: Complementation Cloning Of Sssptamentioning
confidence: 99%
“…long-chain bases ͉ sphingolipids ͉ HSAN1 ͉ ssSPT O riginally thought to be composed of a single subunit, genetic analysis in yeast showed that eukaryotic serine palmitoyltransferase (SPT) is a heterodimer of 2 highly-related subunits, Lcb1p and Lcb2p (1)(2)(3), associated with a third small subunit, Tsc3p, that is required for maximal enzyme activity (4). Based on the crystal structure of 8-amino-7-oxononanoate synthase (5), and the identification of key catalytic residues in other ␣-oxoamine synthases, we proposed that SPT contains a single cytoplasmic catalytic site at the interface of a head-to-tail heterodimer of Lcb1p and Lcb2p comprised of residues from both subunits (6).…”
mentioning
confidence: 99%
“…The Ca 2ϩ -sensitive phenotype of the csg2 mutant was suppressed by several mutations that caused a reduction in the IPC-C concentrations (6). These mutations included genes involved in long chain base synthesis (lcb1, lcb2, tsc3, and tsc10) (6,9,15), palmitoyl-CoA synthesis (fas2) (9), elongation of very long chain fatty acids (tsc13) (9,16), conversion of DHS to phytosphingosine (sur2) (1), and hydroxylation of very long chain fatty acids (scs7) (1). Moreover, overproduction of Ccc2p, which may stimulate the conversion of IPC-C to IPC-D, also rescued the Ca 2ϩ -sensitive phenotype of the csg2 mutant (3).…”
Section: Discussionmentioning
confidence: 99%